Painting Myths With Literature: fantasy as (sub-)creation in “Leaf by Niggle” and in “On Fairy-Stories”, by J. R. R. Tolkien - Zôrro, Iolanda de Brito e (2014)
Technology has shortened geographical distances. We do not deny the paramount position technology has occupied in the political, economical and cultural milieux. However, we likewise recognize that it has been the main reason responsible for the deciphering of the mysteries still left for Humanity to disclose. Thus begins what we will call the twilight of Mankind. With few secrets left to unravel, human beings have had to come up against the extinction of their faith and belief. For Tolkien, the answer to this anguish could be found in the sort of fantastic literature that draws on myth. As such, literature brings back to Mankind pieces of the now lost mythological mystery of the beginning of times. Both “Leaf by Niggle” and “On Fairy Stories” emphasize Tolkien’s description of the literary creative process, comparing it to a contemplative state of awe, to a divine act. Literature, at its core, is an act of mythological (sub)-creation for it sub-creates a world where Recovery, Escape and Consolation become, in fact, real. We aim to prove that myth, fantasy and literature are organically linked and that this trinity has been helping Mankind to survive in a world that is becoming void of mysteries.